DESIGN OF LOST PILGRIM MONITORING APPLICATION WITH ANDROID LBS - Ramadhani, Dwi Randi; Sisephaputra, Bonda (Universitas Negeri Surabaya, 2026)
Muslims who are able, both physically and financially. However, the implementation of this worship often faces challenges, especially for pilgrims who get lost or separated from the group. Based on data, the number of pilgrims reported lost every year reaches thousands of cases, with one of the main contributing factors being overcrowding, language barriers, and complex environments. To overcome this problem, this research aims to design and develop an Android-based HajjWayFinder application by utilising the Location Based Services (LBS) method using the React Native framework and Firebase Firestore. The HajjWayFinder application is designed to assist mentors in monitoring the movement of pilgrims in real-time, tracking the location of lost pilgrims, and facilitating communication through the Panic Button feature. Using the Extreme Programming (XP) method approach, this application is developed with an iterative cycle to ensure functionality and user needs are met. Black-box testing showed that the application was able to run well, both in terms of main features and user interface. The results show that this application can reduce the time and effort required by the mentor to find lost pilgrims. In addition, this application helps improve the solemnity of the Hajj pilgrimage by minimising the stress and panic experienced by pilgrims. The implementation of this technology is expected to make a significant contribution in supporting the implementation of a more organised and effective Hajj.